Redesign UI/UX Sistem Informasi Akademik Satya Wacana Menggunakan Metode Design Thinking - Wijaya, Ricky Arindra; Susetyo, Yeremia Alfa (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Academic website is a technology that can help students obtain information about lectures. The Satya Wacana Academic Information System is an academic website used by Satya Wacana Christian University. Becoming an educational institution with high competitiveness in the quality of science and technology is the vision and mission upheld by UKSW. SIASAT is expected to help UKSW students to compete. Some of the issues complained about by the students is that SIASAT inability to keep up with technological advancements, lack of responsiveness, need for updates, and performance improvements. Therefore, the researchers proposed a solution to redesign the SIASAT website using the design thinking method. The design thinking method was chosen because it focuses on identifying user problems and providing solutions. Design thinking has five stages including Empathize, Define, Ideate, Prototype, and Testing. In the testing stage, UKSW students were given a questionnaire using the System Usability Scale method to assess the feasibility of the redesign, resulting in a "Good" category with a Grade Scale of "B".